Analysis of Consumer Behavior on Purchasing Meat Pork at Traditional Markets in Pematang Siantar City - Tanjung, A. M.; Daulay, Armyn Hakim; Nevy Diana Hanafi (Talenta Publisher, 2021)
Pork consumers prefer it because it has a unique taste. This study aims to determine the factors that influence meat pork consumer behavior and determine the potential segmentation of consumers in traditional markets. The study was conducted in the traditional markets of Pematangsiantar City, namely Horas and Dwikora Parluasan traditional market. It lasted from September 2020 until November 2020. In this study, primary data was obtained from observations and interviews with 70 consumers of meat pork buyers in traditional markets. Secondary data were obtained from related agencies such as the Central Bureau of Statistics and Animal Husbandary Department. The results showed that the characteristics of consumers influenced the potential segment of consumers in meat pork purchasing decisions. The variables of quality and number of families show a relationship of partial influence with the amount of consumption in the analysis of consumer behavior. However, the variables of age, occupation, education, income, and price of pork do not show a partial relationship with consumption.